INSTAGRAM DAN PEMBENTUKAN CITRA (Studi Kualitatif Komunikasi Visual dalam Pembentukan Personal Karakter Account Instagram @basukibtp) - Rama Kertamukti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
See attitude ahok in reality and being displayed in instagram strengthen the identity of human beings that could have been capricious hanging from the interaction with others, instagram used as the merger characteristic of personal and objectives to others through the show that made.With the concept of the theory of dramaturgy used in uncover ahok is very right , role-play which a person does it will create the conditions the interaction that then give them the meaning of its own. In purport visual on instagram dramaturgis with the concept of , depends also purport with background social society that the handling, in the concept of visual called an image that was captured and perceived.